(untitled) (World Economics and Finance Bulletin, 2024)
The theory of information processing for the processes of learning, acquisition and information processing has brought about a scientific and information revolution in the time of the explosion of information in front of the human being who has entered the third millennium in order to have passable ways to invest his creative mental energies in the acquisition of information. This is because he has a composite memory system of long and short, fast preservation and retrieval, slow storage, and forgetfulness and fading of information. All these characteristics affect the levels of learning and processing of information as well as influence the external environment in man and processing information despite the capabilities possessed by the individual, which encouraged to addressing it in the three detectives. So, the aim of this research is to identify the concepts, strategy and components of the theory of information processing and the application of these concepts on the practical side of the organizer predecessor and his ability to exploit his sensory and cognitive qualifications in the processing of information and analysis accurately and applied in one of the formations of the Middle Euphrates Technical University/Ministry of Higher Education/Al-Musayyib. The Technical Institute includes twelve departments, seventeen divisions, and service units, including the research sample which is the Financial Division/Records Unit for the month of November/2008 and the most important findings of the researcher. The organizer uses the all strategies of information processing theory by twinning the information acquired from sensory receptors and stored in memory acquired skills resulting from the work experience about the advances (month of research sample) after classifying them in a specific application for the movement of advances and the stage of different documents (exchange, record, box) down to the results and his skill in solving any existing problem based on retrieving the information stored in his memory